Back Cover: Luminescent nano‐bioprobes based on NIR dye/lanthanide nanoparticle composites. Issue 5 (22nd October 2021) - Lu, Shan; Ke, Jianxi; Li, Xingjun; Tu, Datao; Chen, Xueyuan
Abstract : NIR dye / lanthanide nanoparticle (LnNP) composites have been rapidly developed in recent years and present a great prospect as versatile nano‐bioprobes. This review focuses on the energy transfer mechanisms and the interface engineering in NIR dye/LnNP nanoprobes as well as their applications on luminescent bioimaging, biodetection and multi‐modal theranostics. ( Aggregate . 2021;2:e59 )